Back school and postural habits of women from the Tabajara indigenous community: a quali-quantitative, participatory, and ethnographic approach (Research, Society and Development, 2022)
Objectives: The Back School is a therapeutic-pedagogical method for the preservation of good postural habits, reeducation of posture and prevention of pain in the spine. To know the postural habits of the Tabajara indigenous community through the realization of a sensitization workshop on care of the spine. Methods: This is an action, participatory and ethnographic research with a qualitative/quantitative approach. Fourteen women aged between 18 and 70 years participated. The instruments were inventory of correct and incorrect postural images and postural assessment form. Conclusion: The sum of the posture frequency was 165 to inadequate postures and 92 for appropriate postures. Qualitative analysis highlights that in the CIs of the questions: What are your expectations regarding this work? 78.6%= Learning the new; Have your expectations been met? 92.8%= Learning; Did the spine theme addressed contribute to improve your self-knowledge? 85.7%= Correct use of the spine; How do you feel at the end of the event? 85.7%= Emotional satisfaction; Pain in your spine? 85.7%= feel pain. Practice implications: The study showed that there is involvement in the spine with pain, which may be related to inadequate postures, and it can change using education for health approach.